Comparative systematic review of the psychometric properties of measures of illness perceptions in family members of individuals diagnosed with a chronic physical illness. Issue 1 (31st January 2020) - Fletcher, Chloe; Flight, Ingrid; Gunn, Kate; Patterson, Pandora; Wilson, Carlene
Abstract : Although illness perceptions have significant implications for psychological morbidity in those diagnosed with a physical illness, the strength of this relationship in their family members remains understudied. The validity of findings is dependent on the quality of the instruments used; therefore, it is essential that psychometrically robust measures of illness perceptions are available. The purpose of this systematic review was to identify, assess and compare the psychometric properties of instruments designed to measure illness perceptions in family members of individuals with chronic physical illnesses. A systematic search was conducted using MEDLINE, PubMed, CINAHL, Scopus and PsycINFO databases, and supplemented with forward and backward searches. Studies were included in the review if they described the development, adaptation or psychometric evaluation of an instrument designed to measure illness perceptions in family members of an individual with a chronic physical illness. The methodological quality of included studies was assessed using the COSMIN Risk of Bias checklist. The psychometric quality of instruments was evaluated using published quality assessment criteria. Eleven articles describing nine different instruments were included in the review. Almost all instruments were designed for parents of a child with a chronic illness. There was wide variation in the quality of methods used to develop, adapt or evaluate the instruments, and missing information restricted the evaluation of psychometric properties. Further validation is needed for all instruments before meaningful conclusions can be drawn. Findings indicate that measurement of illness perceptions in children or siblings of an individual with a chronic physical illness has been largely ignored. Future research addressing this gap would be an important addition to the current body of work examining illness perceptions in family members.